A comparison of slide-audiotape and Web-based instructional formats for teaching normal intraoral radiographic anatomy. - Fleming DE; Mauriello SM; McKaig RG; Ludlow JB (Journal of Dental Hygiene)
PURPOSE: The purpose of this study was to evaluate the relationship between individual learning styles, test performance, and attitudes toward the use of Web-based self-instruction and slide/audiotape self-instruction METHODS: Participants consisted of 33 junior, first-year dental hygiene students enrolled in a university-based dental hygiene program. A stratified random allocation (by gender, English as a second language, and prior dental experience) and random number table were used to assign participants into one of two groups. Group one studied the mandibular arch using the slide/audiotape format and the maxillary arch using the Web-based format, and group two studied the mandibular arch using the Web-based format and the maxillary arch using the slide/audiotape format. A post-test was taken at the completion of each instructional format. The Kolb Learning Style Inventory was used to assess preferred learning styles, and a written survey was used for instructional format preference. Descriptive analyses, Pearson correlations, and unpaired t-tests were used to analyze the data. RESULTS: Thirty-one subjects completed the study. By group, no difference in mean post-test performance was seen based on the sequence or order of instructional method (P > 0.05) or by arch (P > 0.05). No difference in post-test performance based on Web-based and slide-tape instructional methods was seen. Predominate learning style did not predict preference of instructional format nor were they correlated with post-test scores. However, almost 70% of all participants reported that they preferred using the Web-based format to the slide/audiotape. CONCLUSIONS: A variety of learning styles and preferences may be accommodated when substituting Web-based self-instruction for slide/audiotape self-instruction in normal radiographic anatomy.